ESTETIKA VISUAL DAN MAKNA TOPENG BABAKAN PANCA WANDA GAYA SLANGIT PRODUKSI HOME INDUSTRY WAS GALLERY CIREBON - Octaviani, Agnes; Syarif , Muh. Ibnan (Eduarts: Jurnal Pendidikan Seni, 2024)
Babakan Panca Wanda mask is one of the traditional arts used in Cirebon mask dance performances. Babakan Panca Wanda Mask as a work of traditional fine art has values and meanings implicit in its visual structure and aesthetic value. This research aims to explain the visual structure, aesthetic value and meaning contained in the Babakan Panca Wanda mask. The research uses descriptive qualitative methods with data collection techniques through observation, interviews and document study. The data obtained was then analyzed through the stages of data reduction, data presentation and drawing conclusions. The research results show that the Babakan Panca Wanda mask consists of five types of masks, namely Panji, Samba, Rumyang, Tumenggung and Kelana. Based on its visual structure, the Panji mask, Samba and Rumyang are classified as one type of wanda with a gentle and kind character, while the Tumenggung and Kelana masks have wanda with an authoritative and strong character. The visual structure is structured based on fine art principles and Javanese aesthetic values, such as the value of order, placement according to categories and the value of harmony.Babakan Panca Wanda mask has a connotative meaning related to cosmological values, symbolic classification and life value orientation, such as religious and family values. Apart from that, it also describes the character and stages of human life from birth to old age. It is hoped that this research can provide advice to mask craftsmen who can continue to preserve the art of the Babakan Panca Wanda mask by passing it on to the next generation.